2022
DOI: 10.1038/s41598-022-07965-z
|View full text |Cite
|
Sign up to set email alerts
|

One-year clinical results of restorations using a novel self-adhesive resin-based bulk-fill restorative

Abstract: This prospective study assessed the dual-curing self-adhesive bulk-fill restorative Surefil one. The restorations were placed and reviewed by dental practitioners who are members of a practice-based research network in the United States. Seven practitioners filled 60 cavities (20 class I, 19 class II and 21 class V) in 41 patients with Surefil one without adhesive, according to the manufacturer’s instructions. The restorations were evaluated using modified USPHS criteria at baseline, 3 months, and 1 year. Pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…51,52 There are also newly introduced self-adhesive bulkfill composites that can eliminate the need for an intermediate material and can be used as a one-piece restoration alternative. 53,54 In another recent study, researchers found that acid etching significantly increased SARC bond strength at different time intervals, whereas using a self-etch adhesive decreased it. 49 Although the RMGIC used in this study did not require acid etching according to the manufacturer's recommendations, acid etching was applied to one of the RMGIC groups, which resulted in increased μSBS values.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…51,52 There are also newly introduced self-adhesive bulkfill composites that can eliminate the need for an intermediate material and can be used as a one-piece restoration alternative. 53,54 In another recent study, researchers found that acid etching significantly increased SARC bond strength at different time intervals, whereas using a self-etch adhesive decreased it. 49 Although the RMGIC used in this study did not require acid etching according to the manufacturer's recommendations, acid etching was applied to one of the RMGIC groups, which resulted in increased μSBS values.…”
Section: Discussionmentioning
confidence: 98%
“…51, 52 There are also newly introduced self-adhesive bulkfill composites that can eliminate the need for an intermediate material and can be used as a one-piece restoration alternative. 53, 54…”
Section: Discussionmentioning
confidence: 99%
“…This might need long established clinical experiences (3,15) and a variety of complex clinical cases in educational and training programs of undergraduates and junior clinicians. Post restoration hypersensitivity and tooth vitality have been listed among the FDI biological properties of ranking restorations (16,17) . Therefore, the current study has used those two parameters for assessing the biological reliability of partial caries removal procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There are still few studies regarding the use and real effectiveness of Surefil One. An annual clinical study by Rathke et al of 60 reconstructions in 41 patients reported encouraging data [ 36 ]. The reconstructions were evaluated at 3 months and 1 year.…”
Section: Discussionmentioning
confidence: 99%